2016
DOI: 10.1681/asn.2014111124
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning-Defective 1a/b Depletion Impairs Glomerular and Proximal Tubule Development

Abstract: The kidney is a highly polarized epithelial organ that develops from undifferentiated mesenchyme, although the mechanisms that regulate the development of renal epithelial polarity are incompletely understood. Partitioning-defective 1 (Par1) proteins have been implicated in cell polarity and epithelial morphogenesis; however, the role of these proteins in the developing kidney has not been established. Therefore, we studied the contribution of Par1a/b to renal epithelial development. We examined the renal phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…Proximal tubule dilation is a common pathological abnormality in urinary tract obstruction, acute kidney injury, and renal dysplasia [24, 44, 45]; of these, acute kidney injury is considered a hyperoxia-induced lesion [13]. We found that neonatal hyperoxia contributed to abnormal proximal tubule dilation in adult rats.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Proximal tubule dilation is a common pathological abnormality in urinary tract obstruction, acute kidney injury, and renal dysplasia [24, 44, 45]; of these, acute kidney injury is considered a hyperoxia-induced lesion [13]. We found that neonatal hyperoxia contributed to abnormal proximal tubule dilation in adult rats.…”
Section: Discussionmentioning
confidence: 88%
“…Proximal tubular cells differentiate from the distal domain of S-shaped bodies during nephrogenesis [24]. HIF-1 α and catalase expression in S-shaped bodies was investigated in order to identify the initial response of proximal tubular cells to neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of having a large set of subjects, a clear genetic correlation with kidney disease was not made. Another study examining the genome-wide cytosine methylation pattern of tubular epithelial cells micro-dissected from human kidneys of control and DKD subjects identified changes in the methylation levels predictive of altered gene expression levels of important renal transcription factors [114]. Exact mechanism for upregulation of Notch pathway is unknown at this time.…”
Section: Human Kidney Diseases Associated With Altered Notch Signamentioning
confidence: 99%
“…[51][52][53] The importance of podocyte polarity signaling is also supported by the high level of redundancy of the involved molecules. [54][55][56] In addition, loss-offunction mutations in the gene encoding the polarity protein CRUMBS2 have been shown to result in steroid-resistant nephrotic syndrome. 57…”
Section: Actin Cytoskeletonmentioning
confidence: 99%